(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
In this article, public procurement plays an important role in the project financing system formed on the basis of public opinion in our country. How public procurement is used in this system and how these systems can meet the needs of society, support social development and reduce corruption. At the same time, it was explained that the openness and competitiveness of the public procurement system allow for the effective and fair distribution of financial resources in Uzbekistan.